A Cross-sectional Study to Evaluate People's Knowledge, Attitude and Practice Towards Using Disinfectants and Sanitizers During COVID-19 Pandemic in Bangladesh - Rintu, Koma Afrin; Prattay, Kazi Milenur Rahman; Sikdar, KM Yasif Kayes; Rahman, Tanvir; Sarkar, Md Raihan; Hossain, Tanveer (Dhaka University Journal of Pharmaceutical Sciences, 2022)
The devastating novel coronavirus (COVID-19) pandemic worldwide has become a global health crisis. This disease is highly contagious and caused by the transmission of severe acute respiratory syndrome, coronavirus 2 (SARS-CoV-2). To prevent the transmission of SARS-CoV-2, disinfectants and sanitizers are very effective and readily available preventive agents. In this study, knowledge, attitude and practice (KAP) levels of Bangladeshi people's were assessed regarding the use of disinfectants and sanitizers during the pandemic. An online questionnaire-based survey was conducted among the respondents from July 2021 to December 2021. A total number of 428 respondents participated in this survey. Data were analysed by the Statistical Package for the Social Sciences (SPSS) V26 software and interpreted. Results revealed that most of the respondents were knowledgeable, had a positive attitude and engaged in beneficial practice. Among the respondents, a significantly higher knowledge and practice score were observed among females (54.1% and 54.4%, respectively) than their counterpart. Moreover, people living in urban areas (71.7%) had a better attitude than the rural people (28.3%). In addition, a medium positive correlation between knowledge and attitude (r = + 0.482), a weak positive association between attitude and practice (r = +0.199), and a weak positive association between knowledge and practice (r = + 0.282) were found. Overall, majority of the respondents had better KAP scores in knowledge and attitude with relatively low scores in practice which indicates some space for betterment. Dhaka Univ. J. Pharm. Sci. 21(2): 117-126, 2022 (December)